Open Economies Review - Tavlas, George S.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
The topics covered in Open Economies Review include, but are not limited to, models and applications of (1) trade flows, (2) commercial policy, (3) adjustment mechanism to external imbalances, (4) exchange rate movements, (5) alternative monetary regimes, (6) real and financial integration, (7) monetary union, (8) economic development and (9) external debt. Open Economies Review welcomes original manuscripts, both theoretical and empirical, dealing with international economic issues or national economic issues that have transnational relevance. Furthermore, Open Economies Review solicits contributions bearing on specific events on important branches of the literature. Open Economies Review is open to any and all contributions, without preferences for any particular viewpoint or school of thought. Open Economies Review encourages interdisciplinary communication and interaction among researchers in the vast area of international and transnational economics. Authors will be expected to meet the scientific standards prevailing in their respective fields, and empirical findings must be reproducible. Regardless of degree of complexity and specificity, authors are expected to write an introduction, setting forth the nature of their research and the significance of their findings, in a manner accessible to researchers in other disciplines. Officially cited as: Open Econ Rev.
Keywords: Macroeconomics; International economics; European Economic Community literature; Economic policy; Development economics; International Economics; Development Economics; European Integration; Macroeconomics/Monetary Economics//Financial Economics; Economic Policy